Kết hợp các phép toán hình thái học và làm mánh để nâng cao chất lượng ảnh đường nét - Toàn, Đỗ Năng; Tạo, Ngô Quốc (Journal of Computer Science and Cybernetics, 2016)
This paper present a method of using morphology operations such as Dilation. Erosion and thinning technique for improving feature images. In general, the morphology operations are used for increasing or reducing the thickness of lines, smoothing contours or filling holes in images. Unfortunately, the erosion operation creates dot lines. In order to overcome this shortcoming, we use the dilation operation and thinning technique step by step. This approach is useful for reducing the thickness of lines and keeps the connectness of lines. The first points of LOOP are suitable chosen for process speed. The paper also shows kinds of maps that can be vectorized and have been tested by the software package MAPSCAN developed in the Department of Pattern Recognition and Knowledge Engineering such as: - Topography, hydrography and transport maps etc... - Technical, designing and electronic circle drawings, finger images etc...